2020
DOI: 10.1016/j.ipm.2020.102354
|View full text |Cite
|
Sign up to set email alerts
|

Promoting users’ intention to share online health articles on social media: The role of confirmation bias

Abstract: Highlights Users with a high level of eHealth literacy are more likely to share positive health articles when they have extreme confirmation bias. Users with a high level of eHealth literacy are more likely to share negative health articles when they have moderate confirmation bias or no confirmation bias. Users with a low level of eHealth literacy are more likely to share health articles regardless of positive or negative content valence when they have mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 52 publications
1
41
0
2
Order By: Relevance
“…Notably, the level of information literacy was found to affect users' engagement in health information seeking (Chang et al, 2015;Quinn et al, 2017). A study by Zhao et al (2020) confirmed these results. The study showed that users with high information literacy share positive health information, while users with a low level of information literacy tend to share information regardless of its authenticity.…”
Section: Health Information Needs In the Age Of Covid-19mentioning
confidence: 55%
“…Notably, the level of information literacy was found to affect users' engagement in health information seeking (Chang et al, 2015;Quinn et al, 2017). A study by Zhao et al (2020) confirmed these results. The study showed that users with high information literacy share positive health information, while users with a low level of information literacy tend to share information regardless of its authenticity.…”
Section: Health Information Needs In the Age Of Covid-19mentioning
confidence: 55%
“…A contributing factor that might enhance the availability bias is the tendency of posting health articles on social media. Levels of confirmation bias in health professionals have been shown to influence which articles are shared on social media (Zhao, Fu & Chen, 2020).…”
Section: Empirical Data On the Prevalence Of Decision-making Biases In Medicinementioning
confidence: 99%
“…However, the low-health literacy assumption of patients should be re-considered in the online situation, driven by three unique characteristics of E-health: (1) Active online engagement: Patients with high health literacy tend to actively engage in online health-related activities, such as health information seeking and use [ 62 ]. (2) Learning and sharing: Patients accumulate more knowledge from online activities.…”
Section: Hypothesis Developmentmentioning
confidence: 99%